Implementasi Kebijakan Pemenuhan Hak-Hak Penyandang Disabilitas di Kota Makassar - Muhammad Afdal Karim (Departemen Ilmu Pemerintahan Fisip Unhas, 2018)
The purpose of this research is to know and analyze the implementation process of Regional Regulation Number 6 of 2013 in Makassar about the fulfillment of the rights of people with disability in Makassar city, and also factors that influence the process of implementation of the regulation. The method used is a qualitative research method, that is giving description or explanation about data acquisition research procedure, data obtained from interview, observation, and archive. Based on the results of the research, the role of Makassar city government in giving protection rights and the right of empowerment of women and children with disability has been implemented by the regional work units into the sample in the research, namely the Social Department of Makassar, empowerment implemented through empowerment program for women with disability, skills such as sewing, baking and crafting. The process of protecting women and children with disabilities is implemented by the Center for Integrated Women Empowerment and Children of Makassar (P2TP2A), protection is provided through the process of assistance and handling cases of violence, exploitation, discrimination and neglect. Overall implementation of the policy of fulfilling the right of empowerment and the protection of its implementation has not been maximally due to several factors. The supporting and inhibiting factors; First, the supporting factors are communication factor, resource (staff) and disposition; Secondly, inhibiting factors are Bureaucracy Structure (SOP and Fragmentation), resources (budget) and external factors (social environment).